Understanding intrinsic phonon thermal transport in two-dimensional γ-GeX (X = S, Se, Te) from first principles - Qiang Fan; Jianhui Yang; Yiding Liu; Weibin Zhang; HaiJun Hou; Ning Wang (Results in Physics, 2023)
Motivated by the recent experimental synthesis of a new hexagonal two-dimensional GeSe material, γ-GeSe, we systematically investigated the phonon transport properties of two-dimensional IV-VI compounds γ-GeS, γ-GeSe and γ-GeTe using first principles calculation and phonon Boltzmann transport equation. We discussed the basic phonon transport properties, including phonon spectra, group velocity, relaxation time, Grüneisen parameter, scattering phase space, phonon mean free path, potential energy change with respect to atomic displacement, and electron localization function of the three compounds. The intrinsic phonon thermal conductivities of γ-GeX (X = S, Se, Te) are quite low due to the low phonon velocity and large phonon scattering rates. Among the three compounds, γ-GeSe gives the lowest thermal conductivity (4.73 W/mK, at room temperature). The relative atomic mass difference between Ge atom and Se atom for γ-GeSe is the smallest which gives decreasing both the phonon relaxation time and phonon mean free path. This behavior is demonstrated by correlating the phonon dispersion and scattering mechanism of each compound. Besides, the potential energy change with respect to atomic displacement and the distribution of electron localization indicating the anharmonicity of γ-GeSe. This work reveals the low thermal conductivity of the two-dimensional γ-GeX (X = S, Se, Te), shedding light on future study and adding additional feature for thermal applications of two-dimensional IV-VI material.